PERAN PENDIDIKAN AGAMA ISLAM TERHADAP BUDAYA VIRAL DAN KRISIS MORAL KALANGAN PEMUDA DI ERA DIGITAL - Eko Sumardianto; Toha Makhshun; Asmaji Muchtar (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) in addressing the moral crisis triggered by viral culture among youth in the digital era. Using a qualitative approach with a descriptive-analytical library research method, the study explores how social media has reshaped youth values, identity, and moral orientation toward a culture of popularity and social validation. The findings reveal that viral culture weakens integrity and spirituality, leading to impulsive behavior and moral decline. Islamic Religious Education plays a strategic role as a moral and spiritual compass by strengthening digital literacy grounded in Islamic ethics, integrating religious values into learning, and empowering teachers as digital role models. Revitalizing PAI through adaptive curricula, technology-based learning innovations, and collaboration among schools, families, and communities is essential to form a digitally intelligent, ethically responsible, and spiritually grounded generation. This study concludes that PAI is not merely a religious subject but a transformative force in building moral and spiritual awareness amidst the rapid flow of digital culture.